Penatalaksanaan Holistik ISK Pada Karyawan Perempuan Melalui Pendekatan Kedokteran Keluarga - Andri Theja; Nicolaski Lumbuun (CV. Jasa Sukses Abadi, 2023)
Urinary tract infection (UTI) is one of the most common types of infection among female employees. Some of the factors that make female employees more susceptible to UTI are the anatomy of the female urinary tract that is different from men, such as the urethra being shorter and closer to the anus, making it easier for bacteria to ascend into the urinary tract. In addition, sexual activity, lifestyle and work environment can also play a role in increasing the risk of UTI in female employees. UTI is a common health problem among women and is often found in primary care. UTI in female employees can cause physical discomfort and negatively impact work productivity. Holistic management and a family medicine approach can provide significant benefits in the management of UTIs especially in female employees who generally due to work demands often hold back urination and lack of drinking water. In the family medicine approach, doctors involve the patient's family in planning and supporting the patient's care. Families and patients are given information about UTIs, symptoms to watch out for, and preventive measures that can be taken. In addition, holistic management also includes psychosocial aspects by providing emotional support to patients and families. Through the family medicine approach and holistic management, it is hoped that patients will gain a better understanding of their condition, experience symptom improvement so that patients do not experience chronic UTI and prevent complications so that they do not need to be referred to secondary care. This approach also helps build a strong relationship between the patient, family and family doctor, which contributes to long-term management and prevention of recurrent infections.